Parenting after Weight Loss Surgery: A Conceptual Model and Two Case Reports. Issue 4 (11th December 2019) - Gibbs, Elise L.; Runfola, Cristin D.; Dickens, Caroline E.; Welch, Hannah; Safer, Debra L.; Sadeh‐Sharvit, Shiri
Abstract : The ways families approach eating, shape, and weight can result in stress for individual family members and challenge the overall functioning of the family. This is further complicated among families with a parent who has history of obesity or undergone weight loss surgery (WLS). Although WLS can positively impact other family members, it can also exacerbate conflicts regarding feeding and weight. Such conflicts can involve uncertainty regarding the extent to which the entire family should make the dietary changes recommended for the post‐WLS parent. Conflict might also center on the appropriate level of concern regarding the children's risk of developing (or maintaining) obesity. This paper uses two case examples to describe the application of a specialized, time‐limited intervention: Parent‐Based Prevention following Bariatric Surgery (PBP‐B). The program was developed to address the unique challenges and concerns that arise after, or are exacerbated by, WLS. Each detailed case example illustrates a common child‐feeding challenge and the employment of key PBP‐B strategies throughout the course of treatment. In the first case, the parent who had undergone WLS believed the family's current eating behaviors were the same as those that had led to her own overeating, obesity, and co‐occurring psychiatric symptoms, while her husband disagreed. In the second case, both parents were concerned about their son's weight, yet due to their prior eating histories, they felt unable to construct boundaries around the feeding experience. Both cases follow families through the entire intervention and illustrate key points and challenges. These cases underscore the need for novel treatment modalities to support families following parental WLS. Abstract : Las maneras en las que las familias abordan la alimentación, la figura y el peso pueden causar estrés en los integrantes individuales de la familia y poner a prueba el funcionamiento general de la familia. Esto es aun más complicado entre las familias con un padre que tiene antecedentes de obesidad o que se sometió a una cirugía para adelgazar. Aunque la cirugía para adelgazar puede repercutir de manera positiva en otros miembros de la familia, también puede exacerbar conflictos con respecto a la alimentación y al peso. Dichos conflictos pueden consistir en la incertidumbre con respecto al grado en el cual toda la familia debería hacer los cambios alimentarios recomendados para el padre que se ha operado para adelgazar. El conflicto también podría centrarse en el nivel adecuado de preocupación en relación con el riesgo de los niños de desarrollar (o mantener) la obesidad. Este artículo utiliza dos ejemplos de casos para describir la aplicación de una intervención especializada y limitada temporalmente: "La prevención basada en los padres después de una cirugía bariátrica" ( Parent‐Based Prevention following Bariatric Surgery, PBP‐B). El programa se desarrolló para abordar los desafíos y las preocupaciones particulares que surgen después de la cirugía para adelgazar o que son exacerbados por esta. Cada ejemplo de un caso detallado ilustra un desafío común con respecto a la alimentación de los niños y al empleo de estrategias fundamentales de la PBP‐B a lo largo del transcurso del tratamiento. En el primer caso, la madre que se había sometido a la cirugía para adelgazar creía que los comportamientos alimentarios actuales de la familia eran los mismos que los que la habían conducido a su propia sobreingesta, obesidad, y síntomas psiquiátricos concomitantes, mientras que su esposo no estaba de acuerdo. En el segundo caso, ambos padres estaban preocupados acerca del peso de su hijo, sin embargo, debido a sus antecedentes alimentarios previos, se sentían incapaces de establecer límites en torno a la experiencia alimentaria. Ambos casos siguen a las familias durante toda la intervención e ilustran puntos clave y desafíos. Estos casos subrayan la necesidad de incorporar modalidades innovadoras de tratamiento orientadas a apoyar a las familias después de la cirugía para adelgazar de uno de los padres. Abstract : 一个家庭对待饮食、体形和体重的方式会对家中某单个家庭成员带来一定的压力，并挑战该家庭的整体运作。对于父母中曾有肥胖病史或进行过减肥手术（WLS）的家庭而言，情况则更加复杂。尽管WLS可以对其他家庭成员产生积极的影响，但也可能加剧在喂养和体重方面的矛盾。此类冲突可能涉及为了遵循给WLS后的父母推荐的饮食，整个家庭应在多大程度上相应调整改变的不确定性。冲突也可能集中有关对儿童患肥胖症（或维持肥胖症）的风险的适当关注上。本文使用两个案例来描述专门的限时干预措施的应用：减肥手术后基于父母的预防（PBP‐B）。该程序的开发主要是针对解决在进行WLS之后出现的或者加剧的独特挑战和特殊问题。每个详细的病例示例都说明了常见的儿童喂养方面的挑战以及在整个治疗过程中如何采用关键的PBP‐B策略。在第一种情况下，经历过WLS的母亲认为家庭目前的饮食行为与导致自己暴饮暴食、肥胖和与此同时出现的精神病症状的行为相同，而她的丈夫则不同意。在第二种情况下，父母双方都担心自己儿子的体重，但是由于他们以前的饮食历史，他们感到无法在喂养经历周围建立边界。这两个案例跟踪了在整个干预过程中的家庭表现，并阐明一些关键点和难点。这些病例强调需要新的治疗手段来支持父母做过WLS后的家庭。